2022
DOI: 10.25259/ijpp_228_2022
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in heart rate variability before and after percutaneous coronary intervention in patients with ischaemic heart disease

Abstract: Objectives: Heart rate variability (HRV) is the beat-to-beat variation of heart rate and an important non-invasive tool to study the cardiac autonomic nervous system activity. Ischaemic heart disease (IHD) patients are often considered to have a state of sympathetic predominance. Elimination of myocardial ischaemia with percutaneous coronary intervention (PCI) could restore autonomic balance. Hence, this study aimed to evaluate HRV measures, after successful revascularisation among IHD patients. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…decreased after PCI, but not LF (n.u.) or LF/HF ratio, although SDNN also decreased [ 32 ], contrary to another study [ 28 ], where the HF (ms 2 ) increased after PTCA;nevertheless, these studies are not comparable due to the methodological differences in the measurement of HRV indices. However, in our study, regarding frequency–domain measures we found differences only in the LF and HF indices measured on power units (ms 2 ) but did not find any significant differences in the LF and HF indices in normalized units (n.u.)…”
Section: Discussionmentioning
confidence: 91%
“…decreased after PCI, but not LF (n.u.) or LF/HF ratio, although SDNN also decreased [ 32 ], contrary to another study [ 28 ], where the HF (ms 2 ) increased after PTCA;nevertheless, these studies are not comparable due to the methodological differences in the measurement of HRV indices. However, in our study, regarding frequency–domain measures we found differences only in the LF and HF indices measured on power units (ms 2 ) but did not find any significant differences in the LF and HF indices in normalized units (n.u.)…”
Section: Discussionmentioning
confidence: 91%